Class conflicts, defense of rights and social work = Conflitos de classes, defesa de direitos e serviço social - Hillesheim, Jaime (Textos & Contextos (Porto Alegre))
Based on Marxian and Marxist assumptions, in particular, the contributions of György Lukács to law as ideology, we try to elicit reflection on the current theoretical and practical challenges to social service to prevent the profession from seeing its ethico-political project capitulate in view of the intensification of the capital offensive against labor. In this paper, the contradictions of the social worker’s work in defending and extending rights vis-a-vis the own logic of bourgeois sociability are discussed. We address the challenges imposed by the limits of such sociability, which require, to be faced, an understanding of critical social theory, given its potential to contribute to professional work in line with the values and principles of the aforementioned project